Mainstreaming the Nationally Appropriate Mitigation Actions (NAMAs) into long-term development plans; Its impact on sustainable development in Non-Annex I Party states - Issaka, Sule Ayannor (Eximia, 2023)
Though the importance of the Nationally Appropriate Mitigation Action (NAMA) in mitigating Global emissions have been covered extensively by the literature, however, there has been little effort by researchers to find out the connections between the successful implementation of the NAMAs of respective Parties and sustainable development in the long run. This paper, based on the results from expert interviews via Skype and telephone with the NAMA focal persons of Ethiopia, Indonesia, and Georgia seeks to fill this gap in the literature by finding out how NAMAs, when implemented can lead to the attainment of overall economic growth and sustainable development in the long run. The paper covers seven NAMAs, with three seeking support for preparation and the other four seeking support for implementation as shown in table 1 below. The findings of this paper have shown significant connections between the NAMAs of the countries under study and overall economic growth based on their impact on the performance of other sectors of their respective economies when successfully implemented. This will contribute significantly to the achievement of sustainable development goals by poorer countries. There is, therefore, the need for developed countries to intensify their support in the areas of capacity building, financial, and technical support to poorer countries to enable them successfully implement their NAMAs as recommended by the Cancun agreement.